2009
DOI: 10.3174/ajnr.a1897
|View full text |Cite
|
Sign up to set email alerts
|

Marchiafava-Bignami Disease with Widespread Lesions and Complete Recovery

Abstract: SUMMARY: MBD is a rare disorder strongly associated with alcoholism. It is characterized pathologically by demyelination and necrosis of the corpus callosum. MBD presents with severe neurologic deficits and significant sequelae developing in most survivors. We report a patient with total clinical recovery. Serial MR imaging demonstrated typical lesions with restricted diffusion in the acute stage and total resolution without atrophy or cystic change.ABBREVIATIONS: ADC ϭ apparent diffusion coefficient; DWI ϭ di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 5 publications
4
43
0
2
Order By: Relevance
“…11,12 High signal intensity on DWI occurs due to reduced diffusion capacity of the surrounding tissue, as caused by swollen myelin sheaths, 13 which suggests a reversible lesion. 14,15 There are some reports that such lesions can be effectively treated with steroids. 9,16,17 Tao et al reported a 16-year-old, female patient with anorexia nervosa and MBD who showed a complete response when treated with methylprednisolone (1000 mg/day for three days).…”
Section: Discussionmentioning
confidence: 97%
“…11,12 High signal intensity on DWI occurs due to reduced diffusion capacity of the surrounding tissue, as caused by swollen myelin sheaths, 13 which suggests a reversible lesion. 14,15 There are some reports that such lesions can be effectively treated with steroids. 9,16,17 Tao et al reported a 16-year-old, female patient with anorexia nervosa and MBD who showed a complete response when treated with methylprednisolone (1000 mg/day for three days).…”
Section: Discussionmentioning
confidence: 97%
“…MRI is the most sensitive tool for the diagnosis of MBD [2][3][4]. In the acute phase, a part or all the corpus callosum appears as a high signal intensity lesion on T2, FLAIR, and DWI imaging, reflecting both oedema and early demyelination.…”
mentioning
confidence: 99%
“…Other nonvascular etiologies noted included infection, especially toxoplasmosis, anoxic injury, posterior reversible encephalopathy syndrome, hemorrhage, liver failure, and paraneoplastic disorders. Although restricted diffusion in the CC has been described in association with Marchiafava-Bignami disease, [14] hypoglycemia, and antiepileptic drug use, [2] these specific causes were not noted within our series.…”
Section: Discussionmentioning
confidence: 55%